Estudio de impacto ambiental del área minera guarapo cód. 6905890, ubicada en la parroquia La Victoria, cantón Macará, provincia de Loja para la fase de exploración avanzada. - Ordóñez Monge, Edison Josue (2015)
In this research it was carried out an environmental impact study of the mining AREA "GUARAPO cod. 690580 ", TO THE ADVANCED EXPLORATION STAGE. Thhe Guarapo is a mining area that is at the stage of advanced exploration for metallic minerals in the canton Macará. The area is located in the parish of La Victoria, canton Macará, province of Loja, with a study of 231 hectares of mining area. To carry out the project, was the description of advanced exploration activities, such as geochemistry, geophysics, drilling and galleries postage, was also the description of the baseline, where was the area on the aspects: climate, vegetation, uses of soil, geology, topography, water, soil and air quality. Within the biotic environment the analysis of areas of life, as well as the flora and fauna existing in the sector, and for the socio-economic area it was analysed the El Guarapo district, which is indirectly affected by the activities of the concession. To be able to determine the physical, biotic and social sensitivity of the sector. The results obtained lead us to the identification, evaluation, and assessment of impacts in order to obtain the environmental opinion and perform under those aspects the plan of environmental management for the environmental impact study. El Guarapo district, which is indirectly affected by the activities of the concession. The purpose was to be able to determine the physical, biotic and social sensitivity of the sector. With the the results obtained it was identify the evaluation, and assessment of impacts to obtain the environmental opinion and perform under those aspects the plan of environmental management for the environmental impact study.